Evaluasi Kejadian Infeksi pada Pasien Luka Bakar yang Dirawat Inap di RSUD dr. Zainoel Abidin - Mahdani, Wilda; Syamsul Rizal; Mirnasari Amirsyah (Journal of Medical Science, 2022)
This study examines the prevalence of infection in burn patients as represented by the clinical spesimen culture results. The purpose of this study was to obtain data on the prevalence, distribution and susceptibility pattern of microbes isolated from clinical spesimens of burn patients hospitalized at RSUD dr. dr. Zainoel Abidin. This study is descriptive observational. The retrospective data obtained from the Plastic Surgery Department and the Clinical Microbiology Laboratory. The results showed the prevalence of infection in burn patients who were hospitalized at RSUD dr. Zainoel Abidin based on clinical spesimen culture of 4.7%. Microbial patterns isolated from burn patients were Gram positive bacteria (37.5%) consisting of Staphylococcus aureus and Staphylococcus hominis. Gram negatif bacteria (62.5%) isolated consisted of Acinetobacter baumannii, Pseudomonas aeruginosa and Klebsiella pneumoniae. The clinical spesimens that showed the most bacterial growth were pus followed by blood and joint fluid. Patients with less than 40% wound area, showed the growth of Staphylococcus aureus, Acinetobacter baumannii and Klebsiella pneumoniae. Patients with wound area above 40%, showed the growth of Staphylococcus aureus, Staphylococcus hominis, Acinetobacter baumannii and Pseudomonas aeruginosa was found. The group of Gram positive bacteria had good sensitivity to the antibiotics vancomycin (100%), linezolid (100%), tigecycline (100%), clindamycin (66.7%), tetracycline (66.7%) and trimethoprim-sulfamethoxazole (66, 7%). The group of Gram negatif bacteria showed high sensitivity to Amikacin (100%).